Status and influencing factors of emotional labour among Chinese psychiatric nurses: a cross-sectional study - Yue Sun; Xiaofen Li; Zhiying Wan (BMJ Open, 2025)
Objectives This study aimed to assess the current status and influencing factors of emotional labour among psychiatric nurses in China, with the goal of informing managerial intervention strategies.Design A multicentre, descriptive, cross-sectional survey was conducted from 22 September 2022 to 20 October 2022.Setting The study was carried out in Hubei province, China.Participants A total of 251 psychiatric nurses from eight general and specialised hospitals participated.Primary and secondary outcome measures Emotional labour was the primary outcome measure. Secondary outcomes included burnout, perceived organisational support and employment-related happiness. Data were collected using a convenience sampling method via Questionnaire Star on WeChat. The questionnaire included demographic information, the Emotional Labour Scale, the Perceived Organisational Support Scale, the Maslach Burnout Inventory and the Nurses’ Employment Happiness Scale.Results Psychiatric nurses reported a moderate level of emotional labour (mean score 45.52 ± 12.50 out of 84). Multiple regression analysis identified subjective job satisfaction as the strongest predictor of total emotional labour. Emotional exhaustion and job satisfaction were significantly associated with all three emotional labour dimensions. Specifically, emotional exhaustion increased surface acting and emotional expression, while higher job satisfaction was associated with increased deep acting and overall emotional labour. Additionally, better interpersonal relationships and benefits packages were associated with more authentic emotional expression.Conclusions Psychiatric nurses in China experience a moderate level of emotional labour. Personal life circumstances and higher subjective job satisfaction may positively influence emotional labour, highlighting key areas for managerial support and intervention.